PELATIHAN KERAJINAN KERTAS BEKAS SEBAGAI MEDIA PEMBELAJARAN KEWIRAUSAHAAN UNTUK SISWA SD 101506 MUARATAIS III TAPANULI SELATAN - najmi hayati harahap; Khairunnisa Butar-Butar; Langgeng Risky Anna; Lina Nafdela Tanjung; Egina (LPPI UMN AL WASHLIYAH, 2025)
The development of entrepreneurial skills from an early age is an important step in instilling independence and creativity in children. One effective method is to use hands-on activities based on recycling as a learning medium. Activities like this allow students to learn about the usefulness of an object, the importance of innovation, and the potential to create something valuable from seemingly useless materials, such as used paper. This community service activity aims to provide training in making crafts from used paper to students of SD 101506 in Muaratais III Village. The implementation method is conducted through a participatory educational approach that directly involves students in the training process. The results of the activity show that students are very enthusiastic in participating in the training and are able to produce creative works from used paper. This activity not only supports entrepreneurship learning, but also fosters care for the environment. It is hoped that this training can become a sustainable program and be applied in school activities.